METHODOLOGICAL ASPECTS OF THE METROLOGICAL SUPPORT FOR THE DETERMINATION OF THE COMBUSTION OF THE PROCESSED NUCLEAR FUEL IN THE PROCESS OF OVERLOADING - Mokritskij, V.A.; Maslov, O.V.; Banzak, O.V. (Збірник наукових праць Військового інституту Київського національного університету імені Тараса Шевченка, 2018)
The article deals with the issues of metrological support of methodology for controlling burn-out of spent nuclear fuel in real time during congestion. The peculiarity of the technique is that for calculating the burnout, no preliminary knowledge of the initial enrichment and holding time is required. The sources of error, the stages of information processing, which can lead to the appearance of an additional error are determined. The analysis made allowed estimating the errors of determination of burn-up and suggest ways of reducing the error. On the basis of the results obtained, a technique for controlling the burn up of spent nuclear fuel in real time during maintenance service is proposed. The peculiarity of the technique is that for calculating the burnout, no preliminary knowledge of the initial enrichment and holding time is required.